Market-based monetary policy expectations for Turkey - Fatih Akçelik; Anıl Talaslı (Central Bank Review (CBR), 2020)
This study discusses various types of market-based instruments and tries to find which financial instrument is the best in predicting monetary policy expectations for different time horizons in Turkey. Consistent with the existing literature on this subject, we adopt an approach that comes from expectations theory of term structure of interest rates, which implies that short term forward interest rates reflect market expectations of short term rates in the future. By using this methodology, we treat upcoming monthly, 3-months, 6-months, 9-months, 12-months, and 24-months average of daily CBRT effective policy rates as alternative dependent variables; and market rates with corresponding maturities as independent variables. We aim to assess which market rate has the best predictive power for CBRT effective policy rates. We find that FX forward implied rates dominate all other instruments for 3, 6, 9, 12 and 24 months horizons while Borsa Istanbul overnight repo rate expectation from CBRT's Survey of Expectations is the best for 1-month horizon in forecasting future policy rates. We also note that CBRT's monetary policy predictability also changes with CBRT's choice of monetary policy implementation.
Keywords: E43; E52; G12; 330; Monetary policy; Policy rate expectations; Market-based measures of expectations